Storage stability of physical and biochemical parameters of pressurized and heat treated nam prig nhum (Thai-green-chili paste) - P. Chaikham (2018)
© 2015 Akadémiai Kiadó, Budapest. Alteration of physical and chemical qualities of pressurized and heat treated Nam Prig Nhum (Thai-green-chili paste) was thoroughly assessed upon storage for eight weeks. During storage, colour L, -a∗, and b∗ parameters of pressurized Nam Prig Nhum displayed comparatively low changes. The enzyme activities of peroxidase, lipoxygenase, and polyphenol-oxidase nearly fell by half during storage. Peroxidase was the most resistant to pressure followed by lipoxygenase and polyphenol-oxidase. For pungent components, all capsaicinoids in Nam Prig Nhum underwent alteration by the thermal processes as well as by acidic and oxidative degradation during storage. However, higher amount of capsaicinoids were retained in pressurized than in heat treated products.